Quinoidal azaacenes: 99 % diradical character - Intorp, Sebastian; Hodecker, Manuel; Müller, Matthias; Tverskoy, Olena; Rosenkranz, Marco; Dmitrieva, Evgenia; Popov, Alexey A.; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2020)
Quinoidal azaacenes with almost pure diradical character (y=0.95 to y=0.99) were synthesized. All compounds exhibit paramagnetic behavior investigated by EPR and NMR spectroscopy, and SQUID measurements, revealing thermally populated triplet states with an extremely low-energy gap ΔEST′ of 0.58 to 1.0 kcal mol−1. The species are persistent in solution (half-life≈14-21 h) and in the solid state they are stable for weeks.